LAW ENFORCEMENT OF THE CRIME OF LOSS OF LIFE WITH CHILDREN AS PERPETRATORS IN CASES OF TRAFFIC ACCIDENT VIOLATIONS - Mashendra (Institute Journal and Publication Muhammadiyah University of Buton, 2023)
This study aims to determine the application of criminal provisions for children in traffic accidents that result in loss of life and to find out the responsibility of children in traffic accidents that result in the loss of life of others. The result of the research shows that: (1) The application of the law of children who cause traffic accidents that result in the death of others must be subject to criminal charges expressly in Law Number 3 of 1997 concerning Juvenile Courts, then the provisions of the Criminal Procedure Code apply as a general rule in this case. Based on Article 7 of Law Number 3 of 1997 concerning Juvenile Courts and Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, there is special treatment for children, in the sense that there is a separation between children and adults in the legal system. These two laws were passed in 1997 and 2012 respectively. (2) The form of liability that can be imposed on a child who causes a traffic accident that results in the death of another person is vicarious liability. Because this case was resolved through the concept of restorative justice that uses a diversion pattern. Every child in conflict with the law should follow the juvenile justice process until the final stage.